Emigration Dynamics in the Context of the Syrian Crisis: Exploring Economic Inequality, Class Power, and the Impact of Capitalism on the Syrian Uprising - Waeel Alsaid (Akademik Analiz)
The crisis in Syria, characterized by widespread conflict, displacement, and socio-economic disruption, has led to one of the largest waves of migration in modern history. This paper explores the emigration dynamics within the context of the Syrian crisis, focusing on the interplay between economic inequality, class power, and the influence of capitalism on the uprising and subsequent migration patterns. By examining the pre-crisis neoliberal reforms that deepened socio-economic inequalities, the study highlights how structural inequalities and class stratification shaped both the trajectory of the uprising and the varied migration experiences of different social groups. The analysis shows that neoliberal economic policies disproportionately affected marginalized rural populations and the working class, exacerbating the economic grievances that underpinned the revolutionary fervor. These protests, coupled with the collapse of public services and widespread violence, forced millions of people to migrate, with wealthier classes accessing safer, structured migration routes while poorer groups faced risky and perilous journeys. The paper also addresses the role of capitalism as a structural force in the crisis and shows how global and regional capitalist dynamics have exacerbated vulnerabilities and influenced migration trends. As well, the article also investigates the socio-economic impact of Syrian migration on host countries, particularly through remittances and the integration of refugee labor, reshaping local economies and social dynamics. By situating Syrian emigration within broader theoretical frameworks of inequality, class, and capitalism, this research contributes to a deeper understanding of forced migration in the context of conflict and systemic economic dislocation. The findings underscore the need for comprehensive policy interventions that address the root causes of displacement while fostering equitable support mechanisms for refugees and host communities.